LEGAL CERTAINTY OF NOTARY POSITION REGARDING AUTHORITY TO CERTIFY ELECTRONIC TRANSACTIONS - Ida Bagus Wirya Dharma; Putu Andhika Kusuma Yadnya; I Wayan Antara; I Kadek Adi Surya (Warmadewa Press, 2024)
Article 15 paragraph (3) UUJN states that Notaries have other regulated authorities apart from those contained in Articles (1) and (2) which are regulated in statutory regulations. In the Elucidation to Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public, it is stated